Comparative Analysis of US Guidelines for the Management of Cutaneous Squamous Cell and Basal Cell Carcinoma - Amit Mittal; Bharat B. Mittal (Journal of Skin Cancer)
Background. This study presents a comparative analysis of recently published guidelines to manage cutaneous squamous cell carcinoma (cSCC) and cutaneous basal cell carcinoma (cBCC) within the United States (US). Methods. A PubMed database search was performed for the time period between June 1, 2016, and December 1, 2022. A comprehensive comparison was performed in the following clinical interest areas: staging and risk stratification, management of primary tumor and regional nodes with curative intent, and palliative treatment. Results. Guidelines from 3 organizations were analyzed: the American Academy of Dermatology (AAD), the National Comprehensive Cancer Network (NCCN), and the American Society for Radiation Oncology (ASTRO). The guidelines used different methodologies to grade evidence, making comparison difficult. There was agreement that surgery is the preferred treatment for curative cBCC and cSCC. For patients ineligible for surgery, there was a consensus to recommend definitive radiation. AAD and NCCN recommended consideration of other topical modalities in selected low-risk cBCC. Postoperative radiation therapy (PORT) was uniformly recommended in patients with positive margins that could not be cleared with surgery and in patients with nerve invasion. The definition and extent of nerve invasion varied. All guidelines recommended surgery as the primary treatment in patients with lymph node metastases in a curative setting. The criteria used for PORT varied; NCCN and ASTRO used lymph node size, number of nodes, and extracapsular extension for recommending PORT. Both NCCN and ASTRO recommend consideration of systemic treatment along with PORT in patients with extracapsular extension. Conclusion: US guidelines provide contemporary and complementary information on the management of cBCC and cSCC. There are opportunities for research, particularly in the areas of staging, indications for adjuvant treatment in curative settings, extent of nerve invasion and prognosis, and the role of systemic treatments in curative and palliative settings.